2005
DOI: 10.1071/wf05038
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and properties of ash and thermally altered soils after high-severity forest fire, southern California

Abstract: After a century of fire suppression, dense forests in California have fueled high-severity fires. We surveyed mixed conifer forest with 995–1178 trees ha−1 (stems > 10 cm diameter at breast height), and nearby pine–oak woodland having 175–230 trees ha−1, 51 days after a severe burn, to contrast the spatial extent and properties of thermally altered soil at sites with different tree densities. Water-repellent soils were more extensive in forest than woodland. Deposits of white ash, composed largely of calici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
66
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 42 publications
14
66
1
1
Order By: Relevance
“…Ash colour is a key variable to understanding fire severity (Smith and Hudak, 2005;Goforth et al, 2005;Úbeda et al, 2009) and is a clear tracer of ash thickness as we observed here, which confirms previous research in the Mediterranean type ecosystems (Pereira et al, 2011). In all studied plots, black ash was thicker than the light grey or white ash due to the lower degree of combustion that leaves a greater amount of organic material in the ash.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Ash colour is a key variable to understanding fire severity (Smith and Hudak, 2005;Goforth et al, 2005;Úbeda et al, 2009) and is a clear tracer of ash thickness as we observed here, which confirms previous research in the Mediterranean type ecosystems (Pereira et al, 2011). In all studied plots, black ash was thicker than the light grey or white ash due to the lower degree of combustion that leaves a greater amount of organic material in the ash.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies have reported ash thicknesses up to 70 mm in an oak forest burned by wildland fires (Ulery et al, 1993), 60 mm in a mixed pine forest (Goforth et al, 2005), and 17 mm in a mixed fir and larch forest (Woods and Balfour, 2008). However little information is available about fire severity effects on ash thickness and its temporal evolution, and no studies have been conducted on this topic on boreal grassland ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sand is comprised primarily of silicon dioxide; iron oxides make up a small fraction of its composition. High temperatures may cause additional changes in mineralogy that may be less likely to be detected by visual examination (Goforth et al, 2005;Pomiès et al, 1998). Similar effects may occur within the silicon dioxide, which becomes unstable with high temperatures and forms silica polymorphs such as trydimite or cristobalite (Hand et al, 1998;Wenk and Bulakh, 2004).…”
Section: Mineralogymentioning
confidence: 99%
“…In most cases it changes from yellowish brown to reddish brown. This is due to the oxidation of soil iron content from goethite to maghemite or hematite (Goforth et al, 2005;Ketterings and Bigham, 2000). Decomposition of soil particles, especially clay minerals, starts at temperatures above 550°C (Certini, 2005).…”
Section: Introductionmentioning
confidence: 99%